Genetic Improvement of Bacillus licheniformis Strains for Efficient Deproteinization of Shrimp Shells and Production of High-Molecular-Mass Chitin and Chitosan - Hoffmann, Kerstin; Daum, Gabriele; Köster, Marina; Kulicke, Werner-Michael; Meyer-Rammes, Heike; Bisping, Bernward; Meinhardt, Friedhelm (Applied and Environmental Microbiology, 2010)
By targeted deletion of the polyglutamate operon (pga) in Bacillus licheniformis F11, a derivative form, F11.1 (Δpga), was obtained that, along with lacking polyglutamate (PGA) formation, displayed enhanced proteolytic activities. The phenotypic properties were maintained in a strain in which the chiBA operon was additionally deleted: F11.4 (ΔchiBA Δpga). These genetically modified strains, carrying the Δpga deletion either alone (F11.1) or together with the ΔchiBA (F11.4) deletion, were used in fermentations (20-liter scale) aiming at the deproteinization of shrimp shells in order to obtain long-chain chitin. After chemical deacetylation, the resulting chitosan samples were analyzed by nuclear magnetic resonance spectroscopy, size exclusion chromatography, and viscometry and compared to a chitosan preparation that was produced in parallel by chemical methods by a commercial chitosan supplier (GSRmbH). Though faint lipid impurities were present in the fermented polysaccharides, the viscosity of the material produced with the double-deletion mutant F11.4 (Δpga ΔchiBA) was higher than that of the chemically produced and commercially available samples (Cognis GmbH). Thus, enhanced proteolytic activities and a lack of chitinase activity render the double mutant F11.4 a powerful tool for the production of long-chain chitosan.